DECISION SUPPORT SYSTEM FOR ANALYSIS AND FORECASTING STATE OF ENTERPRISE - Bidiuk, P. I.; Kozhukhivskyi, A. D.; Kozhukhivska., O. A. (Radio Electronics, Computer Science, Control, 2013)
Decision support system construction procedure is proposed on the basis of Bayesian network that provides a possibility for estimating and forecasting state of small business in conditions of influence of disturbances of different types and nature. Bayesian network is a powerful probabilistic instrument that is constructed on the basis of experimental data expert estimates. An example of application of the net constructed is provided that touches upon determining strategy of small business.